Energy-saving computation offloading scheme based on Sarsa algorithm in industrial internet of things - Jun SUN; Shangweikang ZHAO (物联网学报)
In order to reduce the total energy consumption of industrial internet of things systems with deadline requirements, a computing offloading scheme based on Sarsa algorithm was proposed.Based on the characteristics of Sarsa algorithm, the energy consumption optimization problem was coupled.The Sarsa algorithm iterated the external state value function, selected the appropriate edge computing server to offload the computing task, and then the particle swarm optimization algorithm solved the resource allocation problem.Finally, the environmental information was updated for the next round of algorithm iteration until the algorithm met the end conditions.The simulation results show that this scheme has faster convergence speed and effectively reduces the system energy consumption.